Unruptured unilateral twin ectopic pregnancy: a rare case report - Gaur, Nayanika; Goyal, Piyush K.; Jha, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Unilateral twin ectopic pregnancy is a rare entity with an incidence of 1 in 125,000 pregnancies. This is a case of a 26-year-old primigravida with a spontaneous unilateral twin ectopic gestation, diagnosed on transvaginal ultrasound, treated laparoscopically by doing unilateral salpingectomy and confirmed with histopathology. The doubt for ectopic pregnancy was raised when the serum β-HCG level was constantly >1500 mIU/ml and serum progesterone level was <5 pg/ml and no intrauterine pregnancy was seen. On a follow-up scan, twin gestational sac was noted in right adnexa along with a large haemorrhagic cyst in the right ovary. On post-surgery follow-up, patient was found to have had complete recovery. This case report discusses the incidence and rarity, yet possibility of twin ectopic gestations, the need for early diagnosis and its management.